Boussinesq modeling of wave processes in field fringing reef environments. (February 2020) - Yao, Yu; Zhang, Qiming; Becker, Janet M.; Merrifield, Mark A.
Highlights: A Boussinesq model is used to reproduce the wave processes in field reef environments. IG waves are generated by breakpoint forcing and normal modes exist across the reef. Shoreline SS waves, IG waves and wave setup are larger with concave surfzone seabed. Shoreline IG waves are more sensitive to phase variation in incident wave forcing. Extreme water levels at 50 m from shoreline can serve as a proxy for wave runup. Abstract: Boussinesq modeling of wave transformation over coral reefs to date focuses mainly on wave dynamics at the laboratory scale using idealized fringing reef profiles with relatively smooth surfaces. To better understand the cross-shore wave dynamics associated with coastal wave run-up in field studies of fringing reefs, a numerical study based on the one-dimensional horizontal (1DH) weakly dispersive, highly nonlinear Boussinesq equations is carried out for two realistic fringing reefs with different reef configurations and roughness characteristics in the Republic of the Marshall Islands. A series of incident wave events are tested and compared to the field observations. The numerical simulations demonstrate that the adopted model reproduces the cross-shore sea and swell (SS) waves, infragravity (IG) waves and wave-induced setup over the rough reef flats, which are the components of wave-driven runup and coastal inundation. The model then is applied to investigate the mechanisms of IG wave generation and normal mode excitation on the reef flat. Finally, the shoreline response of waves to the variations of the surf zone seabed profile and the phase of incident waves is examined via the numerical simulations. The ability to predict shoreline runup based on nearshore pressure measurements also is considered.